On the origin of Latin suffixes in -d- and -es, -itis: case endings, composition, analogy and borrowing - Willms, Lothar (Indogermanische Forschungen, 2016)
This article discusses case endings, composition, analogy and borrowing for the origin of Latin suffixes in -d- and -es, -itis. From pedes, formed on the model of PIE-inherited types of compounds in simple -t-, the suffix -es, -itis spread by analogy to further nouns. Despite the Etruscan borrowing satelles, an Etruscan origin for this suffix is unlikely. Composition and instrumental case endings are the origin of the suffix in d. From the instrumental case endings this suffix spread by analogy. Some new insights into the etymologies for the discussed compound nouns in -d- (custōs, cuspis, cassis) buttress the composition origin.
Gesehen am 20.07.2017